Understanding the Dynamics of Political Communication Participation of Chinese Ethnic Groups in Jakarta: A Phenomenological Study - Ilman Heriyawan; Apsari Kumala Dewi; Lusia Putri Aprilia (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
This study aims to understand the dynamics of political communication participation among the Chinese ethnic community in Jakarta through a qualitative phenomenological approach. Utilizing semistructured in-depth interviews, this research explores the subjective experiences of Chinese individuals in the context of political participation. Participants were selected using purposive sampling techniques, comprising individuals aged 18 and above who have resided in Jakarta for at least 5 years and are actively involved in political activities. The collected data were analyzed using thematic analysis techniques to identify key themes emerging from the participants' experiences. The findings reveal that political communication participation among the Chinese ethnic community is influenced by social, cultural, and historical factors and faces various challenges related to stereotypes and discrimination. This study provides significant contributions to the literature on political participation of ethnic minorities in Indonesia and offers practical insights for policymakers to enhance political inclusivity.